Review of depot aripiprazole for schizophrenia - Motiwala FB; Siscoe KS; El-Mallakh RS (Patient Preference and Adherence, 2013)
Farha Bilal Motiwala, Kim Stasia Siscoe, Rif S El-Mallakh Mood Disorders Research Program, Department of Psychiatry and Behavioral Sciences, University of Louisville School of Medicine, Louisville, KY, USA Abstract: Improving outcomes in schizophrenia generally requires an improvement in medication adherence. One of the most effective interventions to improve adherence is the use of depot formulations of antipsychotic medications. A new depot aripiprazole formulation for the treatment of schizophrenia will be available soon. A review of all publically available information on depot aripiprazole as of November 2012 was performed. One peer-reviewed study on depot aripiprazole is published, and the remainder of the data were presented at international scientific meetings. Depot aripiprazole appears to be both safe and effective in the long-term treatment of schizophrenia. Keywords: aripiprazole, schizophrenia, depot, long-acting injectable, psychosis, treatment